Induction and Characterization of Tetraploid Through Zygotic Chromosome Doubling in Eucalyptus urophylla - Liu, Zhao; Wang, Jianzhong; Qiu, Bingfa; Ma, Zhongcai; Lu, Te; Kang, Xiangyang; Yang, Jun (Frontiers in Plant Science, 2022)
The improvement of plant growth can bring great benefits to the forest industry. Eucalyptus urophylla is an important plantation species worldwide and given that ploidy increases are often associated with plant phenotype changes, it was reasoned that its polyploidization may have good prospects and great significance towards its cultivation. In this study, the zygotic development period of E. urophylla was observed through paraffin sections, and a correlation between the development time of flower buds after pollination and the zygotic development period was established. On this basis, the appropriate time for high temperature to induce zygotic chromosome doubling was determined. Then tetraploid E. urophylla was successfully obtained for the first time through zygotic chromosome doubling induced by high temperature, and the appropriate treatment conditions were determined. The characterization of tetraploid E. urophylla was performed. Chromosome duplication brought about slower growing trees with thicker leaves, larger cells, higher net photosynthetic rates, and a higher content of certain secondary metabolites. Additionally, the molecular mechanisms for the variation in the tetraploid’s characteristics were studied. qRT-PCR results showed that genes mediating the tetraploid characteristics showed the same change trend as that of the characteristics, which verified that tetraploid trait variation was mainly caused by gene expression changes. Furthermore, although the tetraploid had no growth advantage compared with the diploid, it can provide important germplasm resources for future breeding, especially for the creation of triploids.